1954
DOI: 10.1042/bj0560669
|View full text |Cite
|
Sign up to set email alerts
|

Bile pigment formation in vitro from haematin and haem derivatives

Abstract: DEGRADATION OF METHAEMOGLOBIN BY HYDROGEN PEROXIDE 669 in the form of methaemoglobin, but was apparently accounted for as carboxyhaemoglobin after the addition of carbon monoxide and dithionite. 4. The green pigment is distinct from choleglobin, and its formation is not prevented by carbon monoxide, showing that oxyhaemoglobin is not an intermediate in the reaction. We wish to thank Mr B. A. Collett for technical assistance during a part of the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
1

Year Published

1957
1957
1989
1989

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…The spectral results, in agreement with previous reports (Kench 1954), show that cytochrome c withstands the action of ascorbate or agents deriving from ascorbate. The spectral changes of hemoglobin and cytochrome c brought about by hydrazine hydrate are different in rate, hemoglobin reacting approximately 5 times faster.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The spectral results, in agreement with previous reports (Kench 1954), show that cytochrome c withstands the action of ascorbate or agents deriving from ascorbate. The spectral changes of hemoglobin and cytochrome c brought about by hydrazine hydrate are different in rate, hemoglobin reacting approximately 5 times faster.…”
Section: Discussionsupporting
confidence: 93%
“…Initially the light absorption decreases in the range 5W600 nm and increases above 600 nm, but then it decreases generally; during these changes carbon monoxide is evolved (Sjostrand 1952). Cytochrome c, however, resists coupled oxidation with ascorbic acid (Kench 1954). In the present experiments the spectral changes of cytochrome c and the evolution of carbon monoxide from this hemoprotein in the presence of some reductants have been followed. Carbon monoxide has been identified as a degradation product of ascorbic acid.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The failure to demonstrate conversion of oc-oxymesoporphyrin or ,B-oxymesoporphyrin into bile pigment in vivo is consistent with the known stability of porphyrins compared with haems in oxidation experiments in vitro (Kench, 1954). Administrationofa-oxymesoporphyrinwasfollowed by the disappearance of bilirubin from the bile and the rapid appearance of radioactivity; bilirubin reappeared in the bile only when radioactivity had decreased.…”
Section: V4supporting
confidence: 72%
“…One α-carbon in each pyrrole residue and each of the four bridge carbons was found to arise from the methyl carbon of glycine. Shemin and Kumin< 140 > subsequently showed that succinate was incorporated into heme without rearrangement. 4).…”
Section: B the Biogenesis Of Porphyrinsmentioning
confidence: 99%